Binary non-fullerene-based polymer solar cells with a 430 nm thick active layer showing 15.39% efficiency and 73.38% fill factor. Issue 11 (23rd February 2021) - Pan, Feilong; Luo, Mei; Liu, Xuncheng; Jiang, Haiying; Wang, Zhen; Yuan, Dong; Wang, Qian; Qing, Lechi; Zhang, Zesheng; Zhang, Lianjie; Zou, Yingping; Chen, Junwu
Abstract : High hole mobility polymer and Y-series non-fullerene acceptor boost efficiency and fill factor of thick-film polymer solar cells. Abstract : Thickness-sensitive fill factor (FF) is usually encountered by organic active layers with a thickness of several hundred nanometers, which significantly deteriorate the photovoltaic performance of thick-film polymer solar cells (PSCs). Here, paring of high-hole mobility ( μ h ) polymer donor Si25 with benzotriazole-fused Y-series non-fullerene acceptor Y14 is proposed to overcome this challenge. Relative to the electron mobility ( μ e ) of 8.17 × 10 −4 cm 2 V −1 s −1 for the Y14 pristine film, much higher μ e values up to 3.79 × 10 −3 cm 2 V −1 s −1 were demonstrated using Si25:Y14 binary blend films, achieving μ h / μ e of 2.31–3.56. The Si25-induced closer packing of Y14 molecules was observed with the blend film. The high and fairly balanced charge transport-enabled PSCs with 320–600 nm thick active layers to show a low FF decay from 74.69% to 67.46%. Power conversion efficiencies (PCEs) of 15.39% and 15.03% were achieved for 430 nm and 600 nm thick active layers, respectively. The device performances can supply a wide processing window with high efficiency. Delightedly, green solvent o -xylene cast active layers of 400 nm and 530 nm thickness exhibited PCEs of 14.43% and 14.25%, respectively. This study indicates that high μ h polymers and benzotriazole-fused Y-series non-fullerene acceptors are promising candidates to overcome the thickness sensitivity of FF.